Comparative Study about the City Planning Systems in Taiwan (for the Years 1895–1945) and Korea (for the Years 1912–1945) under Japanese Rule - Yasushi, Goto (International Planning History Society Proceedings, 2018)
Some existing studies have argued that the City Planning Orders of Japanese colonies were more advanced than the City Planning Act of Japan. The grounds are the integration of building control and city planning, the open-space district and their continued use by the Republic of Korea and the Republic of China after World War II. However, urban planning and building control were included in one system only to simplify the procedure for formulating orders. Furthermore, the Republics of both Korea and China continued using them for a comprehensive policy and an emergency evacuation, not because of order evaluation. Korea Urban Area Planning Order of 1934 and Taiwan City Planning Order of 1936 were created from the City Planning Act of 1919 and the Urban Area Building Act of 1919, reflecting the operational experience of Japan. These acts and orders have been improved as a group. Case studies of modern city planning in Japan, Korea and Taiwan are valuable references to each other.